Depth super-resolved imaging of infrastructure defects using a terahertz-wave interferometer. (June 2021) - Momiyama, Homare; Sasaki, Yoshiaki; Yoshimine, Isao; Nagano, Shigenori; Yuasa, Tetsuya; Otani, Chiko
Abstract: We present a depth super-resolved 3D imaging method for inspection of defects in walls using terahertz swept-source optical coherence tomography. A depth profile analysis based on an annihilating filter method with noise reduction was applied for signal processing, and the results were compared with those of conventional inverse fast Fourier transform (IFFT) analysis. To evaluate the depth resolution, we measured a plastic step sample with 1 mm thickness, and its front and back surfaces were discriminated. This is corresponding to about 1/3 of the theoretical depth resolution of the conventional IFFT analysis. Moreover, we demonstrated 3D imaging of the void with a 10 mm width behind a ceramic tile and succeeded in reconstructing a significantly sharper cross-sectional void image than in the conventional analysis. Graphical abstract: Image 1 Highlights: THz-wave optical coherence tomography for nondestructive infrastructure inspection. 3D imaging of voids behind a tile using a THz-wave interferometer. Depth super-resolution analysis reconstructs sharper images than conventional method.